Del bullerengue sentao al neo soul (2021)
Afro musical expressions have developed similarly in the different countries of the American continent. “African music (at least that of the cultures that had an impact on the formation of African-American music) is characterized, in general terms, by its“ circular ”construction (synchronous superposition of events and processes that makes the diachronic not refer to us to a “linear narrative”, something that is evident, for example, in the rhythmic construction based, almost always, on polymetry) ”(Cardona. 038.2021) Some of the rhythms are better known than others due to its location and commercial flow. It is possible to find coincidences in interpretations of Afro-Brazilian, Afro-Colombian, Afro-American rhythms to mention a few examples. These similarities arise from having the African continent as a common original point. Neo soul and bullerengue will be taken as objects of study. In this way, establish comparisons from the textural rhythmic logics that move in the binary and ternary rhythmic field, "Superposition of rhythmic, binary and ternary patterns that enter into confrontation, originating rhythms that are perceived as complex." (Gollancz LTD, 1988). The response dynamics of their songs and the sections available for improvisation and conceptual expression of the artist.